2016
DOI: 10.1016/j.neurobiolaging.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA methylation near TREM2 is consistently seen in the superior temporal gyrus in Alzheimer's disease brain

Abstract: Although mutations within the TREM2 gene have been robustly associated with Alzheimer’s disease, it is not known whether alterations in the regulation of this gene are also involved in pathogenesis. Here we present data demonstrating increased DNA methylation in the superior temporal gyrus in AD brain at a CpG site located 289bp upstream of the transcription start site of the TREM2 gene in three independent study cohorts using two different technologies (Illumina Infinium 450K methylation beadchip and pyrosequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…With regards to candidate gene analysis the most remarkable finding was a negative association between methylation at cg25748868 in TREM2 and WMH (standardized regression coefficient = -11,3, p = 3.9-E03); however, this did not survive Bonferroni correction for multiple testing (a <1.1E-03) and neither did any of the other tested comparisons (full data not shown). WMH load has been consistently associated with AD; TREM2 hypomethylation and overexpression have been previously observed when comparing blood samples of AD and controls, while increased TREM2 methylation and hydroxymethylation have been observed in AD brain [34][35][36][37][38]. Overall it is likely that previously identified associations between cell composition and Parkinson's disease as well as methylation and expression changes in ABCA7, TREM2 and SNCA with AD and SNCA methylation with dementia with Lewy bodies are specific for those conditions and thus not present in our dataset [27,34,[39][40][41].…”
Section: Resultsmentioning
confidence: 82%
“…With regards to candidate gene analysis the most remarkable finding was a negative association between methylation at cg25748868 in TREM2 and WMH (standardized regression coefficient = -11,3, p = 3.9-E03); however, this did not survive Bonferroni correction for multiple testing (a <1.1E-03) and neither did any of the other tested comparisons (full data not shown). WMH load has been consistently associated with AD; TREM2 hypomethylation and overexpression have been previously observed when comparing blood samples of AD and controls, while increased TREM2 methylation and hydroxymethylation have been observed in AD brain [34][35][36][37][38]. Overall it is likely that previously identified associations between cell composition and Parkinson's disease as well as methylation and expression changes in ABCA7, TREM2 and SNCA with AD and SNCA methylation with dementia with Lewy bodies are specific for those conditions and thus not present in our dataset [27,34,[39][40][41].…”
Section: Resultsmentioning
confidence: 82%
“…This may also be the case for TREM2, as a recent meta-analysis concluded that increased methylation of the TREM2 promoter region appears to be an invariant feature in the brains of AD patients independently of age and sex [64]. Moreover, this increase in methylation correlates with a higher level of TREM-2 (triggering receptor expressed on myeloid cells 2) activity in the brains of AD patients compared with healthy age-and sexmatched controls [69].…”
Section: Introductionmentioning
confidence: 90%
“…The fact that TREM-2 acts as an ApoE receptor may also be of importance as this allows for an exaggerated effect of the ApoE4 protein in the context of dysfunctional TREM-2 receptors [132]. Moreover, a recent meta-analysis reported that increased methylation of the TREM2 promoter region appears to be an invariant feature in the brains of AD patients independently of age and sex [64]. Moreover, this increase in methylation is associated with a higher level of TREM-2 activity in the brains of AD patients compared with healthy controls [69].…”
Section: Influence Of Trem-2 Elevation In Pmbcsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Smith et al . ). Studies of alterations in MAPT DNA methylation in AD are currently inconclusive, with reports of both AD‐associated hypomethylation (Iwata et al .…”
Section: A Role For Dna Modifications In Ad?mentioning
confidence: 97%